Conflicting perceptions on participation between citizens and members of local government - Mohammadi, Seyed Hamid; Syed Abdul Rashid, Sharifah Norazizan; Nikkhah, Hedayat Allah (Springer, 2018)
There is a growing consensus among citizens and members of local government that citizen participation is desirable for local government. However in practice, there are differing perceptions between them regarding the level and extent of citizen participation. As citizen participation is a multi faceted concept, its meaning is construed differently by both the members of local government and the citizen groups. This paper attempts to describe the conflicts that arise from participation. The paper is based on the study of the process of citizen participation in local government carried out in Torbat-Heydarieh city, Iran. A qualitative research method is seen as the most suitable approach of collecting and analyzing the data. The method employed for data collection in this research is in-depth interviews. In-depth interviews were conducted to gauge the existence of conflicts regarding participation. The findings reveal four areas that give rise to conflicts. This study also attempts to highlight two different views regarding citizen participation; the people-centered view and authority-centered view.